Bilateral vertebral artery stenosis present with vertigo - Kotan, Dilcan (BMJ Publishing Group, 2013)
Of ischaemic stroke patients, about 25% rise from the posterior or vertebrobasilar system. The ischaemia of vertebral arteries may emerge for different vascular pathological reasons, at different localisations and with different clinical findings. Despite its low morbidity and mortality risk, early diagnosis and treatment is of importance. Vertebrobasilar ischaemia symptoms can be observed clinically such as vertigo, tinnitus, double vision, headache, hypokinesis and hearing disorders, etc. In this article, a 42-year-old stroke patient case is presented, who applied to the emergency service with vertigo and then, was diagnosed with bilateral vertebral artery stenosis by means of cranial MR angiography.